Economic Science in Crisis Times - Prieto Bustos, William Orlando; Estupiñán, Joan Miguel Tejedor (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This paper discusses the importance of critical pluralism, responsibility, primun non nocere and caution principles, in a scheme of ethical reflection of economics as a science and as a technique. For this purpose, an institutional analysis of policies, standards and guidelines is carried out in a sample of 10 countries: 8 from Latin America, along with the United States, and England. The main result indicates that the current institutional regime, both legislative and ethical, does not solve the tension generated by private interest and public interest in the professional performance of an economist in a market economy. It is necessary to incorporate a flexible articulation that facilitates a simple and concrete interpretation that guides the improvement of the quality of the private and public service that an economist plays.